2021
DOI: 10.3847/1538-3881/abf439
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Exoplanet Size Distribution: Forming Large Super-Earths Over Billions of Years

Abstract: The radius valley, a bifurcation in the size distribution of small, close-in exoplanets, is hypothesized to be a signature of planetary atmospheric loss. Such an evolutionary phenomenon should depend on the age of the star–planet system. In this work, we study the temporal evolution of the radius valley using two independent determinations of host star ages among the California–Kepler Survey (CKS) sample. We find evidence for a wide and nearly empty void of planets in the period–radius diagram at the youngest … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
57
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 89 publications
6
57
1
Order By: Relevance
“…Notably, the theoretical models mentioned also predict larger sizes for sub-Neptunes at earlier times (particularly in the first 100 Myr). Efforts to age-date known exoplanet host stars are providing emerging evidence that the size distribution of small planets continues to evolve over billions of years (Berger et al 2020;Sandoval et al 2021) and that the precise location of the radius gap evolves on similar timescales (David et al 2021). These results are broadly consistent with expectations from the photoevaporation and core-powered mass-loss models.…”
mentioning
confidence: 99%
“…Notably, the theoretical models mentioned also predict larger sizes for sub-Neptunes at earlier times (particularly in the first 100 Myr). Efforts to age-date known exoplanet host stars are providing emerging evidence that the size distribution of small planets continues to evolve over billions of years (Berger et al 2020;Sandoval et al 2021) and that the precise location of the radius gap evolves on similar timescales (David et al 2021). These results are broadly consistent with expectations from the photoevaporation and core-powered mass-loss models.…”
mentioning
confidence: 99%
“…Planets tend to group into two distinct populations, the so-called super-Earths and sub-Neptunes, with a significant dearth of planets with intermediate radii around 2 R ⊕ . This had been expected from theoretical studies (Lopez et al, 2012;Owen & Wu, 2013) before being observed (David et al, 2021;Fulton et al, 2017;Van Eylen et al, 2018).…”
Section: Introductionsupporting
confidence: 58%
“…Although gas accretion alone is able to reproduce the observed radius gap, it is likely that some planets, especially those at short orbital periods, undergo post-accretion mass loss, further sculpting the exoplanet radius distribution. In fact, observations suggest a change in the radius distribution of exoplanets across ∼1-2 Gyrs (e.g., Berger et al 2020;David et al 2021).…”
Section: Effect Of Mass Lossmentioning
confidence: 99%
“…It is generally expected that photoevaporative mass loss carves out the gap in the first ∼100 Myrs when the stars remain active whereas core-powered envelope mass loss is expected to carve out the gap over a longer ∼Gyr timescale. There is observational evidence that the radius distribution shifts at a statistically significant level across Gyr timescales (e.g., Berger et al 2020;David et al 2021). However, EUV luminosity is expected to decline more slowly compared to X-ray so that photoevaporative mass loss may operate over ∼Gyrs as well (e.g., King & Wheatley 2021).…”
Section: Introductionmentioning
confidence: 99%